HIV prevalence, sexual risk behaviours and HIV testing among female sex workers in three cities in Sri Lanka: Findings from respondent-driven sampling surveys - Ariyaratne Manathunge; Jelena Barbaric; Tomislav Mestrovic; Sriyakanthi Beneragama; Ivana Bozicevic; Zixin Wang (PLoS ONE, 2020)
Sri Lanka has a low-level HIV epidemic. This study aims to provide evidence on HIV, syphilis and hepatitis B (HBV) prevalence, sexual risk behaviours and utilisation of HIV prevention interventions among female sex workers (FSW) in the cities Colombo, Galle, and Kandy. Using respondent-driven sampling (RDS), we recruited a total of 458 FSW in Colombo, 360 in Galle and 362 in Kandy from November 2017 to March 2018. Participants provided biological specimens for testing for infections and completed a behavioural questionnaire. We found no HIV nor HBV infections in Galle and Kandy, and low HIV (0.4%) and HBV surface antigen (0.6%) prevalence in Colombo. FSW in Colombo had higher positivity on Treponema pallidum-particle agglutination test (8.4%) compared to Galle (2.0%) and Kandy (2.5%). About two thirds of FSW heard of HIV in each of the cities. Around 90% of FSW used condom at last sex with a client in both Colombo and Galle, but considerably less in Kandy (57.1%). However, lower proportion of FSW used condoms every time during sex with clients in the past 30 day: 22.9% of FSW in Colombo, 26.6% in Kandy and 68.4% in Galle. Across cities, 17.5%-39.5% of FSW reported being tested for HIV in the past 12 months or knowing HIV positive status. The commonest reasons for never testing for HIV was not knowing where to test (54.2% in Colombo, 41.8% in Galle, 48.1% in Kandy) followed by inconvenient testing location (23.7% in Colombo and 31.1% in Kandy). HIV has not yet been firmly established among FSW in three cities in Sri Lanka, but the vulnerability towards HIV and STIs is substantial. HIV interventions should be intensified by expanding community-based HIV testing approaches, increasingawareness of HIV risks and addressing socio-structural vulnerabilities of FSW to HIV.